A 17-Year-Old Male with Large Retropharyngeal Neurofibroma as the Only Symptom of Neurofibromatosis Type 1 (NF1): A Case Report and Review of Literature - Voss-Hoynes, Heather A.; Mahfooz, Naeem; Ostwani, Waseem (Journal of Pediatric Neurology, 2019)
Retropharyngeal neurofibromas are rarely described in the literature and are commonly associated with severe airway-related symptoms. We report a unique case of a large retropharyngeal plexiform neurofibroma in an asymptomatic 17-year-old male patient. This patient was asymptomatic and presented for lower lip edema secondary to an insect bite. Head and neck imaging demonstrated an extensive retropharyngeal neurofibroma measuring 5.7 cm × 2.2 cm × 6.8 cm. Because of extensive involvement of cervical vasculature, the lesion was not resected in our institution and his care was referred to a large neurofibromatosis type I center.
Keywords: plexiform neurofibroma; retropharyngeal; neurofibromatosis